Molecular and genetic mechanisms of physiological adaptations in high- altitude natives Molecular and genetic mechanisms of physiological adaptations in high- altitude natives - Abolfazl Khademi; Zahra Jahanbakhsh; Mitra Yousefpour; Afsaneh Karami Juyani (فصلنامه ابن سینا)
Physiological properties of adaptation to chronic hypoxia can help the high-altitude natives to overcome oxygen limitations. The protective effects of high altitudes have also been confirmed in experimental studies using the hypobaric chamber. Many factors have been introduced about molecular mechanisms of the protective effects of chronic hypoxia. Studies in the past decades and recent genomic studies have suggested a genetic basis for these physiological adaptations in these areas. It is also known that patterns of genetic variations are different among major populations of high altitudes. This article is a review of the physiological adaptations to chronic hypoxia and its molecular and genetic mechanisms.